Nicked - Anderson, M. T. (Pantheon Books, 2024)
"The year is 1087, and a pox is sweeping through the Italian port city of Bari. When a lowly monk is visited by Saint Nicholas in his dreams, he interprets the vision as a call to action. But his superiors, and the power brokers they serve, have different plans for the tender-hearted Brother Nicephorus. Enter Tyun, a charismatic treasure hunter renowned for "liberating" holy relics from their tombs. The six-hundred-year-old bones of Saint Nicholas rest in distant Myra, Tyun explains, and they're rumored to weep a mysterious liquid that can heal the sick. For the humble price of a small fortune, Tyun will steal the bones and deliver them to Bari, curing the plague and restoring glory to the fallen city. And Nicephorus, the "dreamer," will be his guide. What follows is a heist for the ages, as Nicephorus is swept away on strange tides-and alongside even stranger bedfellows-to commit an act of sacrilege. Based on real historical accounts, Nicked is a wildly imaginative, genre-defying, and delightfully queer adventure, full of romance, intrigue, and wide-eyed wonder at the world that awaits beyond our own borders"--